Validation of chromatographic method for impurity profiling of Baloxavir marboxil (Xofluza) - Wang Yiyun; Wang Zhiping; Wu Hui; Meng Zihui; Zheng Zhonghui; Li Jiarong (Science and Engineering of Composite Materials)
Baloxavir marboxil (BXM) is a new antiviral drug that inhibits the cap-dependent endonuclease required to replicate the virus. The efficacy, quality, and safety of drug products and active pharmaceutical ingredients (APIs) may be compromised by impurities. To ensure the safety and quality of medications, it is essential to test APIs and drugs for impurities. Methods for analyzing and detecting BXM intermediates and impurities are currently unknown. Therefore, it is crucial to implement analytical methodologies and ensure the quality control of intermediates and associated compounds during the medication manufacturing and storage processes. This is necessary to enhance the overall product quality of BXM, improve its therapeutic efficacy, and reduce potential adverse effects. High-performance liquid chromatography (HPLC) was utilized to detect and quantify impurities in BXM and its intermediates in this study. The impurities were removed using column chromatography and characterized using mass spectrometry and nuclear magnetic resonance. Based on the spectral data, the structures of impurities were identified as 3,4-difluoro-2-benzenesulfinyl methyl benzoate and methyl 3,4-difluoro-2-(benzoyl oxymethyl) benzoate. A highly efficient HPLC method was designed and validated to assess its accuracy, linearity, specificity, and precision. As mentioned earlier, the results demonstrated that the methodology exhibits specificity, accuracy, and precision, with a separation degree of ≥1.5, making it suitable for routine analysis. Furthermore, the source of BXM impurities and its intermediates was confirmed by analyzing their underlying mechanism. The separation, structure identification, and mechanistic analysis of impurities are crucial in efficiently managing impurities in BXM and its intermediates. It provides technical assistance for the quality control of BXM, thereby ensuring the drug’s safety.